Promoting speaking in the young learner classroom through task-based digital storytelling via online technology: a case study - Lustenberger Andrea (Journal of China Computer-Assisted Language Learning)
In the young learner (YL) foreign language (FL) classroom, oracy is more important than literacy, but teaching speaking is still primarily repetitive in many contexts. Free speaking activities are difficult to create for teachers and accomplish for learners. This research investigated the ways in which imaginative digital storytelling (DST) tasks can improve oracy and the prior knowledge needed to negotiate meaning. The main data of this study, which were collected over one academic year, comprised a questionnaire of 19 Swiss Year 4 students, video and audio recordings of two dyads working on four collaborative oral DST tasks and a semi-structured interview with the four children and their class/English teacher. The results revealed that collaborative end-of-unit tasks enabled the children to creatively recycle the language learnt. Scaffolding and language support provided on the task sheet allowed a creative and personal approach to DST, which was a motivating experience. Clear guidance for classroom talk fostered collaboration and personal, social and problem-solving competences. These findings have implications for YL FL pedagogy and highlight the need for further theoretical insights into task-based DST.